1998
DOI: 10.1136/jme.24.4.223
|View full text |Cite|
|
Sign up to set email alerts
|

Bioethics of the refusal of blood by Jehovah's Witnesses: Part 1. Should bioethical deliberation consider dissidents' views?

Abstract: Jehovah's Witnesses' (JWs) refusal of blood transfusions has recently gained support in the medical community because of the growing popularity of "no-blood" treatment. Many physicians, particularly so-called "sympathetic doctors", are establishing a close relationship with this religious organization. On the other hand, it is little known that this blood doctrine is being strongly criticized by reform-minded current and former_JWs who have expressed conscientious dissentfrom the organization. Their arguments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…The practice of disfellowshipping has attracted some attention in the Journal of Medical Ethics . Muramoto claims that current WTS practices amount to coercion and argues that the WTS could retain the controversial blood doctrine while instituting a don't-ask-don't-tell policy that would protect individual privacy and autonomy 3. Donald Ridley, a member of the WTS, responds:

Muramoto essentially advances the anarchic notion that, after freely choosing to join an organisation because they have come to share or identify themselves with the organisation's basic values or objectives and after agreeing to abide by its rules and procedures, individuals should nevertheless be free to abandon those values and objectives and reject the organisation's rules and procedures but still insist that the organisation accept them as full and active members in good standing.

…”
Section: Religious Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The practice of disfellowshipping has attracted some attention in the Journal of Medical Ethics . Muramoto claims that current WTS practices amount to coercion and argues that the WTS could retain the controversial blood doctrine while instituting a don't-ask-don't-tell policy that would protect individual privacy and autonomy 3. Donald Ridley, a member of the WTS, responds:

Muramoto essentially advances the anarchic notion that, after freely choosing to join an organisation because they have come to share or identify themselves with the organisation's basic values or objectives and after agreeing to abide by its rules and procedures, individuals should nevertheless be free to abandon those values and objectives and reject the organisation's rules and procedures but still insist that the organisation accept them as full and active members in good standing.

…”
Section: Religious Backgroundmentioning
confidence: 99%
“…This may or may not be occurring and may differ from one community of JWs to the next, just as it does among other Christian communities. If Muramoto is correct, ‘Jehovah's Witnesses have been strongly discouraged from discussing critical religious issues with outsiders, particularly with former members, and can be ‘disfellowshipped’ (excommunicated) for doing so’ (p 223) 3. If this is true of any group (not just JWs), it raises serious doubts about the rationality of its members and leaders.…”
Section: Firmness Of Beliefmentioning
confidence: 99%
“…ajwrb.org]), or should they remain silent regardless of the degree to which they might find the patients' views to be irrational and misguided, so to avoid the perception of "religious interference"? Muramoto [33][34][35][36] and others [37][38][39] have taken the position that truly ethical physicians should inform their patients as fully as possible on all matters affecting their care, seeing any discussions centering on possible religious inconsistencies as merely an attempt to ensure that their patients have the opportunity to be fully informed on an important life-and-death issue. By contrast, Shander 40 has taken the position that one should remain silent on religious issues and focus on purely clinical concerns, citing the difficulties of what he sees as essentially being an attempt at religious conversion.…”
Section: Ethical Issuesmentioning
confidence: 99%
“…Critics of the Watchtower Bible and Tract Society's position on blood transfusion have highlighted the inconsistency of the ban, as some blood products and organ transplants are permitted, and have likened a transfusion to a cellular transplant as opposed to the "eating of blood." 6 Ridley of the Watchtower Bible and Tract Society has addressed these critiques by explaining that Jehovah's Witnesses refuse transfusions based on obedience to scripture. 7 One study has shown that close to 10% of Jehovah's Witnesses would agree to a red blood cell transfusion for themselves if needed.…”
Section: Jehovah's Witnesses and Blood Productsmentioning
confidence: 99%